Rozwiązane

6X-3=7X+1
-9X+1=X-3
7-X=-6X-3
3(X+1)-5=-(X-5)+3
-4(2X-3)+1=8-2(7-3X)



Odpowiedź :

Odpowiedź:

6x - 3 = 7x + 1

6x - 7x = 1.+ 3

-x = 6

x = - 6

-9x + 1 = x - 3

-9x - x = - 3 - 1

-10x = - 4 /:(-10)

x = 0,4

7 - x = -6x - 3

-x + 6x = -3 - 7

5x = -10 /:5

x = -2

3(x + 1) - 5 = -(x - 5) + 3

3x + 3 - 5 = -x + 5 + 3

3x +x = 5 + 3 - 3 + 5

4x = 10 /:4

x = 2,5

-4(2x - 3) + 1 = 8-2(7 - 3x)

-8x + 12 + 1 = 8 - 14 + 6x

-8x - 6x = 8 - 14 - 12 - 1

-14x = - 19

x = - 14/19

Odpowiedź:

6x-3= 7x+1

  6x-7x= 1+3

  -x= 4/*(-1)

     x= - 4

-9x +1 =x-3

  -9x -x= -3-1

    -10x= -4 /*(-1)

  10x=4 /:10

    x= 4/10= 2/5

7-x = - 6x-3

  -x +6x= -3 -7

   5x= -10 /:5

     x= -2

3(x+1) -5= -( x -5) +3

  3x +3-5= -x +5+3

3x+x= 5+3 -3+5

    4x= 10 /:4

      x= 10/4= 2 i 2/4= 2 i 1/2

-4( (2x-3 )+ 1= 8-2( 7-3x)

   -8x +12 +1= 8-14 +6x

 -8x -6x= 8-14 -12-1

 -14x= -19 /*(-1)

   14x= 19 /:14

     x= 1 i 5/14                                                                                                                                                                                                                        

Szczegółowe wyjaśnienie: